2021
DOI: 10.1038/s41392-021-00534-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutant KRAS triggers functional reprogramming of tumor-associated macrophages in colorectal cancer

Abstract: Oncogenic KRAS has been previously identified to act in a cell-intrinsic manner to modulate multiple biological functions of colorectal cancer (CRC). Here, we demonstrate a cell-extrinsic role of KRAS, where KRAS engages with the tumor microenvironment by functional reprogramming of tumor-associated macrophages (TAMs). In human CRC specimens, mutant KRAS positively correlates with the presence of TAMs. Mutationally activated KRAS in tumor cells reprograms macrophages to a TAM-like phenotype via a combination e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 48 publications
2
45
0
Order By: Relevance
“…Cetuximab, an EGFR-targeting agent, is a standard treatment for KRAS wild-type mCRC [ 27 ]. KRAS mutant CRC cells have been reported that it could promote tumour progression and induce resistance to cetuximab therapy [ 28 ]; however, there is no effective treatment to specifically treat cancers expressing KRAS mutations [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab, an EGFR-targeting agent, is a standard treatment for KRAS wild-type mCRC [ 27 ]. KRAS mutant CRC cells have been reported that it could promote tumour progression and induce resistance to cetuximab therapy [ 28 ]; however, there is no effective treatment to specifically treat cancers expressing KRAS mutations [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…HE staining demonstrating the histology of tumors formed in the livers was observed using the ImageScope software as described. 54 …”
Section: Methodsmentioning
confidence: 99%
“…Patients with mutant KRAS tumors had a significantly shorter time to CRPM development and CRPM-free survival compared to those wild-type KRAS status [ 84 ]. Concordantly, Liu et al [ 85 ] demonstrated that mutant KRAS reprograms macrophages to a M2 TAM-like phenotype through colony-stimulating factor 2 and lactate production, which promoted tumor progression and conferred EGFR inhibitor resistance.…”
Section: The Tumor Microenvironment In Crcmentioning
confidence: 96%